Domestic Politics and Norm Diffusion in International Relations Ideas do not float freely - Risse, Thomas (Routledge/UACES Contemporary European Studies, 2017)
This book collects Thomas Risse's most important articles together in a single volume. Covering a wide range of issues - the end of the Cold War, transatlantic relations, the "democratic peace," human rights, governance in areas of limited statehood, Europeanization, European identity and public spheres, most recently comparative regionalism - it is testament to the breadth and excellence of this highly respected International Relations scholar's work. The collection is organized thematically - domestic politics and international relations, international sources of domestic change, and the diffusion of ideas and institutions - and a brand new introductory essay provides additional coherence. This text will be of key interest to scholars and students of International Relations, European Politics, and Comparative Politics.